A comparison of prompting methods to teach sight words to students with autism spectrum disorder. (16th April 2019) - Klaus, Sophie; Hixson, Michael D.; Drevon, Daniel D.; Nutkins, Christie
Abstract : Time delay procedures are one of the most commonly used and effective strategies for teaching sight words to learners with disabilities. However, less is known about whether they are differentially effective and efficient with learners. This study compared the effectiveness and efficiency of progressive time delay and simultaneous prompting on sight word acquisition among three learners with autism spectrum disorder using an adapted alternating treatments design across word sets. For two participants, both procedures led to skill acquisition with no clear differences in efficiency. For the remaining participant, neither procedure was effective; therefore, the reading task was changed to a receptive one, and a stimulus fading intervention package was implemented.